2016
DOI: 10.1016/j.jceh.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Histological Evaluation of Non-alcoholic Fatty Liver Disease and Its Correlation with Different Noninvasive Scoring Systems with Special Reference to Fibrosis: A Single Center Experience

Abstract: Background: Although liver biopsy remains the gold standard for the diagnosis of non-alcoholic fatty liver disease [NAFLD], many non-invasive markers of liver fibrosis have recently been proposed and assessed as surrogates of liver biopsy. Aims and objective: To evaluate the degree of liver fibrosis by different non-invasive fibrosis scoring systems and to compare each non-invasive fibrosis scoring system with histological fibrosis stage. Materials and methods: The study population consists of consecutive pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…In addition, histopathological changes in liver from microscopy observation correlated with the examination of liver function (Rath et al. 2016; Koo et al. 2017).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, histopathological changes in liver from microscopy observation correlated with the examination of liver function (Rath et al. 2016; Koo et al. 2017).…”
Section: Discussionmentioning
confidence: 95%
“…2018), it often developed a histological spectrum starting from simple steatosis to NASH with the characterization of hepatocellular damage, fibrogenesis and lobular necro-inflammation (Rath et al. 2016; Jin et al. 2018), which may evolve to hepatic cirrhosis and HCC (Liu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Non-alcoholic fatty liver disease (NAFLD) presents a spectrum of disorders ranging from simple steatosis and steatohepatitis to fibrosis and cirrhosis [24]. Liver biopsy is a gold standard for diagnosis of liver cirrhosis, however due to its invasive nature noninvasive scoring systems were developed for assessment of fibrosis in patients with NAFLD [25,26]. Rath MM et al concluded that noninvasive scoring systems like NFS, BARD and APRI are not sensitive enough to detect fibrosis, but highly specific to include it for scores higher then specific cut offs [25].…”
Section: Discussionmentioning
confidence: 99%
“…Liver biopsy is a gold standard for diagnosis of liver cirrhosis, however due to its invasive nature noninvasive scoring systems were developed for assessment of fibrosis in patients with NAFLD [25,26]. Rath MM et al concluded that noninvasive scoring systems like NFS, BARD and APRI are not sensitive enough to detect fibrosis, but highly specific to include it for scores higher then specific cut offs [25]. Van Greenen EJ et al conducted a postmortem study on 80 cadavers and found that total pancreatic fat is a significant predictor for presence of NAFLD, but there was no correlation between pancreatic fat and NAFLD activity score [27].…”
Section: Discussionmentioning
confidence: 99%
“…Liver transaminases (ALT and AST) have been widely used in clinical settings to predict the presence of liver diseases including NASH [ 25 ]. Elevations in circulating ALT level are indicative of hepatocyte damage, and ALT is an important component of several composite NASH scoring systems [ 26 , 27 ]. As ALT and microRNAs are independent measurements of liver functions, we then sought to incorporate ALT into the microRNA signature to see if the performance could be further improved.…”
Section: Resultsmentioning
confidence: 99%